DOES COMPUTER ANXIETY HAVE EFFECTS ON ACADEMIC LIBRARY ELECTRONIC CATALOGUE SUCCESS? - Nugroho, Mahendra Adhi (International Business Education Journal, 2010)
This research modifies DeLone and McLean’s (1992) Information system success model by adding anxiety as a factor that have negative. It aims to find out the academic library electronic catalogue success and to explore the direct and moderating effects of computer anxiety. Using 220 academic library electronic catalogue users from four universities, this research explores computer anxiety effects on academic library electronic catalogue success. Before running a hypothesis test a statistical power analysis is made. The aims of statistical power analysis are to reject type 1 and type 2 statistical errors and to get practical significations on hypotheses. This research uses Partial Least Square (PLS) technique to test the research model. The research model is run twice, the first run uses the full research model which (include computer anxiety variable) and the second run uses the model without computer anxiety variable. The first run shows system quality and electronic catalogue system have significant positive correlation to user satisfaction. Another result from the first run is that the electronic catalogue use and user satisfaction have positive significant correlation. Computer anxiety has negative significant correlation to electronic catalogue use but, the hypothesis that shows the negative correlation between computer anxiety and user satisfaction has no significant negative correlation. On the other hand, the moderation role of computer anxiety in correlation between electronic catalogue use and user satisfaction has no significant negative correlation. An interesting phenomenon is found in the second run. In the second run (model without computer anxiety variable), a positive significant correlation between information quality and electronic catalogue use is found. That means information quality has an effect on electronic catalogue use. This cannot be found in the first run (model use computer anxiety variable). That phenomenon shows the role of computer anxiety on Information system success model.